YOUTUBER SEBAGAI PERUBAHAN MINAT PROFESI KAUM MILENIAL DI ERA POSTMODERN - Adinda Fara Adhary; Fahmi Mahmuddin Siregar; Muhammad Rosikhun Abid; Dini Safitri (Prodi Ilmu Komunikasi, FISIP, Universitas Muhammadiyah Cirebon, 2021)
This research discusses how the profession of becoming a Youtuber is a benchmark in professional transition that often occurs in the postmodern era of the present which is especially felt by millennials. The purpose of this research is to find out what things are produced related to being a Youtuber as a professional transition in this post modern era as well as the background of the resulting work commodification and the various views related to the professional transition that occurred. The theory used in this study uses the postmodern Jean-Francois theory. The research approach in this study uses a qualitative approach. The method used in this research is a case study method. The research subjects in this study were millennials who are Youtuber by profession. Data collection techniques in this study used in-depth interviews conducted online with informants. The results of this study indicate that postmodernism influences informants to be involved in the youtube world. There are two statements that have been described by the informants in this study, namely, some of them consider that the profession of being a Youtuber in this post modern era for them is just a side profession on the basis of filling free time and as a hobbyist. Besides that, some of them also think that being a Youtuber is a very promising profession to see the income they receive if they get a large number of followers.Keywords: Youtuber, postmodern, millennials